Rock Mineralogy Analysis of Airbenakat Formation to Map the Characteristics of the Reservoir Rocks in each Depositional Environment - Kharisma Idea; Taufan Marhaendrajana; I GB Eddy Sucipta; Sri Feni (Journal of Petroleum and Geothermal Technology, 2023)
The Airbenakat Formation is a sandstone reservoir which is one of the oil reservoirs located in Sumatra and is part of the South Sumatra Basin. The mineral composition of the sandstone reservoir in the Airbenakat Formation consists of quartz minerals as rock grains, clay as matrix and is often identified as cement, while carbonate as rock cement. Based on lithofacies observations, the depositional environment of the Airbenakat Formation consists of: Volcanic Alluvial Fan, Lake, Braid Bar, Braided Channel, Braid Deltaic Environment, Mud Flat, Tidal Sand Bar, Tidal Environment, Shallow Sea, and Deep Sea. This research was conducted on 2 (two) oil fields, namely MRP dan TPN which have different depositional environments but are included in the Airbenakat Formation as part of the South Sumatra Basin.The analyzes used in this study include X-Ray Diffraction (XRD) analysis, petrography, and Scanning Electron Microscopy with Energy Dispersive X-Ray Spectroscopy (SEM/EDX). Analysis of the mineralogical content of the Airbenakat Formation will assist to determine the performance of chemical injections such as injection of anionic surfactant. The anionic surfactant used for chemical injection in Airbenakat Formations will be optimal if the content of smectite and calcite minerals can be ascertained. The presence of smectite and calcite minerals will affect the results of anionic surfactant injection. This research shows the results of anionic surfactant injection on the presence of smectite and carbonate in the injected core.